Mechanisms for upstream migration of firn aquifer drainage: preliminary observations from Helheim Glacier, Greenland - Jessica Z. Mejia; Kristin Poinar; Colin R. Meyer; Aleah N. Sommers; Winnie Chu (Journal of Glaciology)
Surface meltwater can influence subglacial hydrology and ice dynamics if it reaches ice sheet's base. Firn aquifers store meltwater and drain into wide crevasses marking the aquifer's downstream boundary, indicating water from firn aquifers can drive hydrofracture to establish surface-to-bed hydraulic connections at inland locations. Yet, sparse observations limit our understanding of the physical processes controlling firn aquifer drainage. We assess the potential for future inland firn aquifer drainage migration with field observations and linear elastic fracture mechanics (LEFMs) modeling to determine the conditions needed to initiate and sustain hydrofracture on Helheim Glacier, Greenland. We find that local stress conditions alone can drive crevasse tips into the firn aquifer, allowing hydrofracture initiation year-round. We infer inland expansion of crevasses over the firn aquifer from crevasse-nucleated whaleback dune formation and Global Navigation Satellite System-station detected crevasse opening extending 14 and 4 km, respectively, inland from the current, farthest-upstream drainage point. Using our LEFM model, we identify three vulnerable regions with coincidence between dry crevasse depth and water table variability, indicating potential future inland firn aquifer drainage sites. These results suggest the downstream boundary of firn aquifers can migrate inland under future warming scenarios and may already be underway.